Theoretical Investigation on the Fully Developed Turbulent Heat Transfer Characteristics of Liquid Sodium - Zhang, Rui; Wang, Zhenying; Wang, Zhenhong; Ren, Tingting; Shi, Jiangwu (Frontiers in Energy Research, 2020)
Liquid sodium has been used as the working medium for the high-temperature heat pipe and the generation IV sodium cooled fast reactor due to its extremely high conductivity. The heat transfer characteristics of sodium in a circular pipe is one of the most essential focuses in engineering applications. In this paper, a model to predict the heat transfer coeffcient of fully developed sodium flowing in tube was developed based on universal velocity, turbulent eddy diffusivity, and the linear law inside the thermal boundary layer. The Kays correlation for turbulent Prandtl number was used to predict the turbulent Prandtl in the bulk flow with y + larger than 60. This model was validated by experiment data of Hg, NaK, and sodium, showing superior accuracy than existing models. Besides, the dependence of the accuracy on the model parameters was also analyzed, demonstrating the universal applicability of the current model.